Perancangan Ulang Fasilitas Fisik Kerja Operator di Stasiun Penjilidan pada Industri Percetakan Berdasarkan Prinsip Ergonomi - Taufiq Rochman; Rahmaniyah Dwi Astuti; Fuad Dwi Setyawan (Industrial Engineering Study Program, Faculty of Engineering, Universitas Sebelas Maret, 2012)
Prestasi Agung Pratama Press is a company which produce Lembar Kegiatan Siswa (LKS) forElementary School (SD) and Secondary Junior High School (SMP). The process of the production is print the cover and content, stacking and bookbinding, cutting, finishing and packing. The position of the worker is sit on the floor based on the space. The workers want to sit with comfortable position for example sit on the chair, chair cloth is expected more soft because the work position with sitting continuously. In this research is done with the design of the table and chair by using a study of anthropometry. The seated posture is important from the standpoint of reducing both the stress on the feet and overall energy expenditure. Because comfort is a very individual response, strict principles for good seating are somewhat difficult to define. The design of the table and chair use the data of anthropometry from 20 workers. The research produces the design of the table and chair as follows: for the chair with the size is 51 cm tall, the deep of the chair is 45 cm, 42 cm wide the height of the armchair is 28 cm. Whereas for the table is 72 cm height, 204 cm length, and 108 cm width. Based on the considerating of the room wide availability, the wide of the table – chair and the material supplied for 13 workers who stay in the station of the stacking and bookbinding.